Turkish adaptation, validity and reliability study of the sexual and reproductive empowerment scale for adolescents and young adults - Gül, Sıla; Büyükkayacı Duman, Nuriye (CSIRO Publishing, 2025)
Background This reliability and validity study aimed to adapt the Sexual and Reproductive Empowerment Scale for Adolescents and Young Adults (SRES-AYA) into Turkish, and to introduce it to Turkish society by conducting validity and reliability studies. Methods The sample consisted of undergraduate students between the ages of 18–24 years studying at a university. A 19-question personal information form and the 23-question SRES-AYA were used to collect data on the topic. Data were collected through face-to-face interviews in January 2023. In the scale’s validity phase, language, content and construct validity were examined, respectively. Internal consistency and time invariance were reviewed in the reliability stage of the scale. The data were analysed with the SPSS for Windows 22 package program and the LISREL 8.80 package program. Results The content validity index of the scale was found to be 0.99. The Kaiser–Meyer–Olkin test was 0.874, and Barlett’s test of sphericity significance level chi-squared = 3511.034, P = 0.000. In the exploratory factor analysis, the factor loadings of all items were >0.40, the variance explained was 74.668%, and no items were removed from the scale. The fit index values evaluated in the confirmatory factor analysis were chi-squared/s.d. = 3.71, goodness of fit = 0.98, adjusted goodness of fit = 0.97, comparative fit index = 0.99, root mean square error of approximation = 0.074, standardized root mean square residual = 0.053, and path diagram factor loadings between 0.41 and 0.91, all of which were found to be within the acceptable range. Cronbach’s alpha was 0.913, and Spearman’s Rho coefficient was 0.893. Conclusions The scale was determined to be a valid, highly reliable instrument suitable for Turkish society.